Geochronology, Petrogenesis and Crustal Evolution of the Saglek-Hebron Complex (Northern Labrador): Over One Billion Years of Archean Geological History - Wasilewski, Benjamin (Université d'Ottawa / University of Ottawa, 2019)
The Saglek-Hebron Complex (SHC) in Northern Labrador represents one of the oldest terrains on Earth and it is closely related to the Archean Itsaq Gneiss Complex (IGC) in Greenland. The SHC is a typical granite-greenstone terrain that recorded over one billion years of magmatic history between ~3900 Ma and ~2700 Ma. Our geochronological and geochemical study shows that the SHC includes five generations of trondhjemite-tonalite-granodiorite suites (TTG): the ~3870 Ma Iqaluk gneiss, the ~3750 Ma Uivak I gneiss, the ~3600 Ma Uivak II gneiss, the newly described ~3300 Ma Iluilik gneiss, and the ~3220 Ma Lister gneiss. These granitoid units are mostly consist of trondhjemite and tonalite with only rare granodiorites that appear to define a distinct unit formed at ~3330 Ma and newly defined as the Iluilik gneiss. The Iluilik granodiorite appears to be derived from a Hadean mafic crust as supported by its combined whole-rock geochemical composition, its positive µ142Nd value of +6, and its low εHf= -6 and εNd= -3, at 3300 Ma. SHC granites were emplaced throughout the Archean, from 3800 to 2700 Ma, but are predominant in the Neoarchean. They appear to have been mainly formed from the reworking of the SHC TTG, as supported by their low εHf and εNd initial values of respectively -16 and -11 at 2700 Ma. The granitoids include numerous enclaves of supracrustal rocks from various size, up to a few kilometers in scale, consisting of metavolcanic metasedimentary rocks. Previous work has suggested that they were formed at two different ages, with the younger Upernavik supracrustal unit deposited around 3400 Ma and the older Nulliak supracrustal assemblage deposited at around 3750 Ma. We show that both units are comparatively geochemically homogeneous with no distinction between the mafic and ultramafic rocks from both supracrustal assemblages. They mainly consist of mafic metavolcanic amphibolites with tholeiitic affinities, consistent with more depleted mafic and more enriched compositions produced by magmatic differentiation. Their complementary Eu anomaly and whole-rock geochemistry suggest that they formed from fractional crystallization of gabbroic assemblage that derived from similar if not the same parental magma. The mafic metavolcanic rocks are also often associated with ultramafic rocks that we divided into two distinct units, respectively referred as the high-Fe and the low-Fe ultramafic rocks, characterized by different FeO contents and Al/Ti ratio. They both represent olivine-rich cumulative rocks derived from distinct parental komatiitic basalt magmas. Our interpretation contrasts with previous work suggesting that the SHC ultramafic rocks were komatiites and slivers of residual lithospheric mantle. Most SHC TTG exhibit a positive 142Nd anomaly, as high as µ142Nd = +15, suggesting a source formed by differentiation in the Hadean. This 142Nd isotopic composition is similar to the Nulliak supracrustal rocks that exhibit on average a µ142Nd of +10. TTG is generally considered to derive from a mafic precursor. This study therefore shows that mafic crustal source of the SHC Eoarchean TTG, potentially the Nulliak metabasalts, derives from an ancient highly depleted mantle, described as the Saglek mantle, sharing a similar early history as the mantle reservoir involved in the formation of the ancient Itsaq terrane of southwest Greenland. The Saglek depleted mantle is interpreted to have formed at ~4400 Ma, exhibit highly depleted signature with a 147Sm/144Nd ratio of 0.221-0.240.
Keywords: Saglek-Hebron Complex; Eoarchean Crust; Geochemistry; Geochronology; Isotope; Petrology